THE STATIC DIELECTRIC-CONSTANT OF WATER AT PRESSURES UP TO 20 KBAR AND TEMPERATURES TO 1273-K - EXPERIMENT, SIMULATIONS, AND EMPIRICAL EQUATIONS - Wasserman, E; Wood, B; Brodholt, J (1995)
The static dielectric constant of water was calculated by molecular dynamics simulations using the SPC/E water model up to 1273 K and pressures to 20 kbar. Simulations within the pressure-temperature range (up to 5 kbar and 823 K) of the available experimental data yield dielectric constant (ε) in very good agreement with experiment (within 5%) for all values of density ≤ 1.0 g/cm3. This demonstrates that the SPC/E model provides a valid means of obtaining the dielectric constant beyond the P, T range of the available data. Several previous attempts were made to extrapolate the experimental values of ε to high P, T conditions using semi-empirical fit equations. We tested two of these equations (Pitzer, 1983; Franck et al., 1990) against our simulated values of ε at densities of 0.322, 0.5 g/cm3 and 1.0 g/cm3 for temperatures ranging from 600-1200 K. For density ≤ 1 g/cm3 and temperatures above 600 K the equation of Franck et al. (1990) is in agreement with the simulations to within 7% and provides, therefore, a simple and valid method of extrapolation of the data. © 1995.